Numerical analysis of jerry can strength under static and dynamic loads - Гондлях, Олександр Володимирович; Чемерис, Андрій Олегович; Онопрієнко, Владислав Юрійович (Eastern-European Journal of Enterprise Technologies, 2015)
Such material as high-density polyethylene is used for producing jerry cans, fuel tanks, liquid storage and transportation tanks. Significant shortcomings that may arise in the strength analysis of five-liter jerry cans for storing petroleum products were determined. Based on the APPROX software system using the finite element moment scheme, a system that allows the numerical strength analysis of jerry cans of different shapes and sizes, with the possibility to set different physical and mechanical properties of materials, including composite materials, in a particular statics and dynamics problem statement was implemented. A finite-element model of the jerry can was built, and numerical analysis of the strength under static and dynamic loads taking into account the load nature (stacked storage, kick) was performed. As a result of the numerical analysis, the values of the stress-strain state of the jerry can were obtained, and stress concentration zones were identified. The data is important since it allows to determine the optimal wall thickness for this kind of structures and define optimal storage conditions.